A symmetric sixth-order step-up converter with asymmetric pwm achieved with small energy storage components (2024)
This research explores an improved operation of a recently studied converter, the so-called two-phase sixth-order boost converter (2P6OBC). The converter consists of a symmetric design of power stations followed by an LC filter; its improved operation incorporates an asymmetric pulse width modulation (PWM) scheme for transistor switching, sometimes known as an interleaved PWM approach. The new operation leads to improved performance for the 2P6OBC. Along with studying the 2P6OBC, one of the contributions of this research is providing design equations for the converter and comparing it versus the interleaved (or multiphase) boost converter, known for its competitiveness and advantages; the single-phase boost topology was also included in the comparison. The comparison consisted of a design scenario where all converters must achieve the same power conversion with an established maximum switching ripple, and then the stored energy in passive components is compared. Although the 2P6OBC requires a greater number of components, the total amount of stored energy is smaller. It is known that the stored energy is related to the size of the passive components. Still, the article includes a discussion of this topic. The new operation of the converter offers more streamlined, cost-effective, and efficient alternatives for a range of applications within power electronics. The final design of the 2P6OBC required only 68% of the stored energy in inductors compared to the multiphase boost converter, and 60% of the stored energy in capacitors. This result is outstanding, considering that the multiphase boost converter is a very competitive topology. Experimental results are provided to validate the proposed concept